Efficiency Assessment of Sustainable Urban Drainage Systems at University Campus Trsat (Proceedings of Faculty of Civil Engineering, 2021)
In this paper, an analysis of the stormwater drainage system at the University Campus in Rijeka is conducted. In addition to the classic stormwater drainage system, a sustainable stormwater drainage system has been proposed. The efficiency of this proposal was evaluated using a hydrological-hydraulic model. The results show that the implementation of a sustainable stormwater drainage system can significantly reduce runoff to pre-development levels.
Keywords: stormwater drainage; green infrastructure; design storm